Intestinal microbiota and biliary system diseases - Wang, Hua; Gong, Junfeng; Chen, Jingyi; Zhang, Wei; Sun, Yanjun; Sun, Dengqun (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction The incidence of biliary system diseases has been continuously increasing in the past decade. Biliary system diseases bring a heavy burden to humanity and society. However, the specific etiology and pathogenesis are still unknown. The biliary system, as a bridge between the liver and intestine, plays an indispensable role in maintaining the physiological metabolism of the body. Therefore, prevention and treatment of biliary diseases are crucial. It is worth noting that the microorganisms participate in the lipid metabolism of the bile duct, especially the largest proportion of intestinal bacteria. Methods We systematically reviewed the intestinal microbiota in patients with gallstones (GS), non-calculous biliary inflammatory, and biliary tract cancer (BTC). And searched Pubmed, Embase and Web of science for research studies published up to November 2023. Results We found that the abundance of Faecalibacterium genus is decreased in GS, primary sclerosing cholangitis (PSC), primary biliary cholangitis (PBC) and BTC. Veillonella, Lactobacillus, Streptococcus and Enterococcus genus were significantly increased in PSC, PBC and BTC. Interestingly, we found that the relative abundance of Clostridium was generally reduced in GS, PBC and BTC. However, Clostridium was generally increased in PSC. Discussion The existing research mostly focuses on exploring the mechanisms of bacteria targeting a single disease. Lacking comparison of multiple diseases and changes in bacteria during the disease process. We hope to provide biomarkers forearly diagnosis of biliary system diseases and provide new directions for the mechanism of intestinal microbiota in biliary diseases.